Leader–Member Exchange Fosters Beneficial and Prevents Detrimental Workplace Behavior: Organizational Identification as the Linking Pin - Götz, Martin; Donzallaz, Michelle; Jonas, Klaus (Frontiers in Psychology, 2020)
Discretionary behaviors, such as counterproductive work behavior (CWB) and organizational citizenship behavior (OCB), directly refer to an organization’s normative expectations. As such, employees engaging in these behaviors violate or exceed organizational norms, respectively. An employee’s relationship quality with his or her supervisor (i.e., leader-member exchange [LMX]), has been found to be a prominent antecedent of employees’ workplace behavior. However, the actual mechanisms that link LMX and discretionary behaviors (i.e., CWB and OCB) are not yet well understood. Integrating social exchange as well as the social identity theory, we present an employee’s organizational identification (OI) as a mechanism that sheds light on why LMX leads to employees’ subsequent discretionary behavior. Across four empirical studies employing complementary study designs, we demonstrate that LMX is positively associated with OI which, in turn, curbs CWB and fosters OCB. Specifically, this pattern of findings is consistent across (1) a cross-sectional study with 188 Swiss employees, (2) a time-lagged study with 502 Swiss employees, (3) an online recall experiment with 131 US participants, and (4) an online vignette experiment with 139 US participants. In sum, we present an integrative theoretical model and respective empirical support to shed light on OI as a pivotal mechanism that can explain why the relationship quality with one’s supervisor can simultaneously serve as a deterrent for CWB and foster OCB.